Pengaruh Gaya Kepemimpinan, Remunerasi dan Pendidikan Pelatihan Terhadap Kinerja Pegawai Pada Kantor Pelayanan Pajak Pratama Palembang Ilir Barat - Echi Kurniati (P3M STIE Mulia Darma Pratama, 2020)
This study aims to determine the effect of the Leadership Style (X1) Remuneration (X2) and Education Training (X3) to Performance (Y) Employees at Tax Office Primary Palembang Ilir Barat. Data was collected by questionnaires, which uses Linkert scale compiled and summarized from the various theories, and embodied in the operational variables. Data were analyzed with descriptive and inferential (correlation and regression) using the SPSS program. Hypothesis testing t test for partial correlation and multiple F test for correlation. 95% significance level (α = 0.05). The study population were all employees of the Tax Office Primary Ilir Palembang west numbering 76 people, 44 people for research data and 30 for testing. Sampling techniques are saturated sampling technique. The results of the analysis conducted that the partial correlation coefficient between Leadership Styles on Employee Performance, Employee Performance and Remuneration with Education Training to Employee Performance obtained successively by 0.599; 0.500 and 0.598, while simultaneously the correlation coefficient is 0.725 This shows that the variable -variables studied have a very close relationship. Based on these results in order to improve the performance of employees is expected to be able to pay attention to the dimensions of the variables leadership style, remuneration and Education Training because it has a significant effect on employee performance.